The history of the Kazakh written signs - Akhmediyeva KYbyraimzhanov К, Bekish A, Mailybaeva G, Shengelbayeva S, (Opción)
This article discusses the primary education systems on Kazakh land and the history of written signs, and alphabets based on system descriptions via analysis from a philosophical, historical, sociopolitical and pedagogical-psychological point of view. As a result, Activities carried out in Kazakhstan to translate the Kazakh script into the Latin alphabet, were ill-conceived, they did not solve the problem of the Kazakh alphabet, and it was evident from the experience. In conclusion, there was a reform of the Kazakh script in the system of organization of the educational process in primary school.